Swisher, Ed., The Spread Of Islam; Roded., Ed., Women In Islam And The Middle East - Allen, Calvin (Teaching History: A Journal of Methods, 2000)
These two anthologies have in common an examination of a particular theme, contained in the title, over the entire course of Islamic history from the time of the Prophet Muhammad in Arabia to the present. The similarities end there.